AVERT2 (a very early rehabilitation trial, a very effective reproductive trigger): retrospective observational analysis of the number of babies born to trial staff. (11th December 2015) - Bernhardt, Julie; Lindley, Richard I; Lalor, Erin; Ellery, Fiona; Chamberlain, Jan; Van Holsteyn, John; Collier, Janice M; Dewey, Helen M; Parsons, Brooke; Moodie, Marjory; Lennon, Sheila; Donnan, Geoffrey A; et al.
Abstract : Objective To report the number of participants needed to recruit per baby born to trial staff during AVERT, a large international trial on acute stroke, and to describe trial management consequences. Design Retrospective observational analysis. Setting 56 acute stroke hospitals in eight countries. Participants 1074 trial physiotherapists, nurses, and other clinicians. Outcome measures Number of babies born during trial recruitment per trial participant recruited. Results With 198 site recruitment years and 2104 patients recruited during AVERT, 120 babies were born to trial staff. Births led to an estimated 10% loss in time to achieve recruitment. Parental leave was linked to six trial site closures. The number of participants needed to recruit per baby born was 17.5 (95% confidence interval 14.7 to 21.0); additional trial costs associated with each birth were estimated at 5736 Australian dollars on average. Conclusion The staff absences registered in AVERT owing to parental leave led to delayed trial recruitment and increased costs, and should be considered by trial investigators when planning research and estimating budgets. However, the celebration of new life became a highlight of the annual AVERT collaborators' meetings and helped maintain a cohesive collaborative group. Trial registration Australian New Zealand Clinical Trials Registry no 12606000185561. Disclaimer Participation in a rehabilitation trial does not guarantee successful reproductive activity.